Hubungan Perhatian Orang Tua Terhadap Disiplin Belajar Siswa Kelas V SD - Abd. Kadir A; Rahmawati Patta; Kamaruddin Hasan; abdul malik (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
The problem in this study is the lack of parental attention to students, so students are less disciplined in learning. This study is a quantitative study with a correlation design which aims to determine the relationship between parental attention and learning discipline for fifth grade students in SD Cluster II. The results showed that there was a significant relationship between parental attention to the learning discipline of fifth graders at SD Cluster II with a tcount value of (4.5302) greater (>) ttable value (1.68488), which means H0 is rejected and H1 is accepted. Based on the analysis of the data above, it can be concluded that parental attention will have an impact on student learning discipline. So, the better the parents' attention, the better the student's learning discipline. From these conclusions, the impact resulting from this study is known that good parental attention will improve student learning discipline.